MANAJEMEN STRATEGIS PERGURUAN TINGGI DALAM MENINGKATKAN DAYA SAING DI ERA GLOBALISASI - Saparuddin, Muhammad; Komariyah, Laili; Subagiyo, Lambang; Warman, Warman (FIKRUNA: Jurnal Ilmiah Kependidikan dan Kemasyarakatan, 2025)
The aim of this study is to examine the role of strategic management in enhancing the competitiveness of higher education institutions in the era of globalization, with a focus on private universities in East Kalimantan. The method used is a literature review, analyzing various academic sources and policy documents related to higher education institutional strategies. The findings indicate that long-term vision-based strategic planning, digital transformation, adaptive leadership, internationalization, and good institutional governance are key factors in building institutional competitiveness. The implementation of the Merdeka Belajar Kampus Merdeka (MBKM) Curriculum also significantly contributes to aligning graduates’ competencies with labor market demands. However, challenges such as limited human resources, funding constraints, and inadequate digital infrastructure remain major obstacles, particularly in regions outside Java. This study concludes that integrative and adaptive strategic management is essential for developing globally competitive private higher education institutions.